Nonsaponin fractions of Korean Red Ginseng extracts prime activation of NLRP3 inflammasome - Byung-Cheol Han; Huijeong Ahn; Jiseon Lee; Eunsaem Jeon; Sanghoon Seo; Kyoung Hwa Jang; Seung-Ho Lee; Cheon Ho Kim; Geun-Shik Lee (Journal of Ginseng Research, 2017)
Background: Korean Red Ginseng extracts (RGE) have been suggested as effective immune modulators, and we reported that ginsenosides possess anti-inflammasome properties. However, the properties of nonsaponin components of RGE have not been well studied. Methods: To assess the roles of nonsaponin fractions (NS) in NLRP3 inflammasome activation, we treated murine macrophages with or without first or second inflammasome activation signals with RGE, NS, or saponin fractions (SF). The first signal was nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB)-mediated transcription of pro-interleukin (IL)-1β and NLRP3 while the second signal triggered assembly of inflammasome components, leading to IL-1β maturation. In addition, we examined the role of NS in IL-6 production and IL-1β maturation in mice. Results: NS induced IL-1β and NLRP3 transcription via toll-like receptor 4 signaling, whereas SF blocked expression. During the second signal, SF attenuated NLRP3 inflammasome activation while NS did not. Further, NS-injected mice presented increased IL-1β maturation and IL-6 production. Conclusion: SF and NS of RGE play differential roles in the NLRP3 inflammasome activation. Hence, RGE can be suggested as an NLRP3 inflammasome modulator.